Determinación de tensión arterial, índice de masa corporal, y hemoglobina glicosilada en el debut diabético atendidos en el Centro de Salud n°3 y Lizarzaburu en el período noviembre 2017 – abril 2018 - Barros Barreno, Karen Elizabeth (2018)
The main objective of the present research is to determinate the blood pressure, body mass index, and glycosylated hemoglobin at the onset diabetes. This is a non-experimental study, descriptive, retrospective, with bibliographic- documentary design documentary in which we reviewed the medical records of 94 patients that met the entry criteria. The results of the research suggest that: glycosylated hemoglobin test was carried out in just the 5.38% of patients suggesting the lack of control by using this method. There is a greater prevalence of diabetes in women and in the age range of 46-65 years. Diabetes is prevalent in patients with values of BMI between 30-34.9 which corresponds to obesity type I. The HTA that prevails in the patients with normal and normal high. A little more than half of patients is normotensive. No correlation was found between the HbA1c variables and age and for glucose levels. Demonstrating the inappropriate qualification by the health professionals of first level and the lack of collaboration for the usrs of it where the study was conducted as figures of HbA1c with values of 7.1-9 representing 41.5%, for taking over by the inspection bodies.